Diversity Patterns of Vascular Plants at Varied Elevations in Arghakhanchi, West Nepal - Nepali, Baburam; Skartveit, John; Baniya, Chitra Bahadur (Journal of Plant Resources, 2022)
The genuine image of biodiversity, as well as their germplasm, is visualized by the turnover of species rather than their similarities in each location. The major goal of this study was to determine the b-diversity pattern of vascular plants growing at 100 m contour elevations and to explore its association with a-diversity and elevation. Primary data were gathered utilizing 4-6 10 x 10 m2 quadrats at 100 m contour elevation, on both the south and north sides, in Arghakhanchi district, west Nepal. Beta diversity represents the change in diversity of species between two communities and is measured by two different matrices: species turnover and similarity. Between two adjacent elevational bands, the species turnover was calculated using the Bray-Curtis dissimilarity index and similarity was assessed using the Jaccard index technique in the Vegan package for R version 4.03. The species richness (a-diversity) and b-diversity indices (Bray-Curtis dissimilarity index and Jaccard similarity index) were regressed by generalized linear model (GLM) method with elevation. The species richness and Jaccard similarity index suggests statistically significant unimodal structure with elevation; however, Bray-Curtis dissimilarity index suggests statistically significant but reverse unimodal pattern. As a result, rather than species turnover, the presence of more related species usually creates the peak area of a unimodal pattern of alpha diversity. The geographical scale of biodiversity loss or its effective preservation by human activities is revealed by beta-diversity. Any region with high beta diversity suggests a wide variety of species, which aids in the administration of conservation programs.